2005
DOI: 10.1093/nar/gki303
|View full text |Cite
|
Sign up to set email alerts
|

Two modes of microsatellite instability in human cancer: differential connection of defective DNA mismatch repair to dinucleotide repeat instability

Abstract: Microsatellite instability (MSI) is associated with defective DNA mismatch repair in various human malignancies. Using a unique fluorescent technique, we have observed two distinct modes of dinucleotide microsatellite alterations in human colorectal cancer. Type A alterations are defined as length changes of ≤6 bp. Type B changes are more drastic and involve modifications of ≥8 bp. We show here that defective mismatch repair is necessary and sufficient for Type A changes. These changes were observed in cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 41 publications
2
57
1
Order By: Relevance
“…36,48 Intriguingly, the IC678 tumour also exhibits a MMRdefective phenotype. 49 As shown in Figure 4a, alterations in a human dinucleotide microsatellite, D13S175, were readily detected in the genomic DNA extracted from this tumour. Indeed, a sequence alteration resulting in an amino-acid substitution was found at codon 521 of another essential MMR gene, MLH1 (Figure 4b).…”
Section: Mmr Deficiency In Proofreading-mutant Colorectal Carcinomasmentioning
confidence: 83%
“…36,48 Intriguingly, the IC678 tumour also exhibits a MMRdefective phenotype. 49 As shown in Figure 4a, alterations in a human dinucleotide microsatellite, D13S175, were readily detected in the genomic DNA extracted from this tumour. Indeed, a sequence alteration resulting in an amino-acid substitution was found at codon 521 of another essential MMR gene, MLH1 (Figure 4b).…”
Section: Mmr Deficiency In Proofreading-mutant Colorectal Carcinomasmentioning
confidence: 83%
“…56 In this regard, it is known that MSI results are dependent on the markers chosen for analysis, the threshold chosen for instability, and the sensitivity of the assay used. 34 Although other oncogenic tyrosine kinases, such as BCR/ABL, have been reported to suppress MMR, 52 the mechanisms have not been previously studied. We believe that our study has shed light on the possible mechanisms by which oncogenic tyrosine kinases deregulate MMR.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, we chose four additional monomorphic markers that are mono-nucleotide repeats proved to be informative for the detection of microsatellite instability (MSI) in Lynch associated with the loss of MSH6. [33][34][35] DNA samples were isolated from eight normal donors and nine ALK ϩ ALCL tumors. Tumor DNA was isolated from paraffin curls using the Qiagen Blood and Tissue Kit (Qiagen, Mississagua, ON, Canada).…”
Section: Detection Of Microsatellite Instability In Alk ϩ Alcl Tumorsmentioning
confidence: 99%
“…Recently, novel types of MSI have been reported termed type A and type B alterations. 32 Type A alterations are defined as length changes of 6 bp and type B changes are more drastic modification of 8 bp. In our study on UC specimens, all types of MSI we observed belonged to the type A alterations.…”
Section: Discussionmentioning
confidence: 99%
“…Type A MSI may reflect the uncorrected DNA slippage events that may be related to the MSI-L phenotype. 32 Loss of MGMT is a candidate mechanism for MSI-L CRC. However, loss of MGMT expression was not observed in our study.…”
Section: Discussionmentioning
confidence: 99%